KOMPOSISI DAN KEANEKARAGAMAN ARTHROPODA PREDATOR PADA AGROEKOSISTEM PADI - Hendrival Hendrival; Lukmanul Hakim; Halimuddin Halimuddin (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2017)
The research of predatory arthropod species diversity in agro-ecosystem is very important because it affects the function of natural enemies in suppressing pest population. Management of paddy through cultivation method can be part of the conservation of predatory arthropods. This study was conducted to analyze and compare the diversity of predatory arthropod with method cultivation conventional and integrated crop management (ICM) and diversity predatory arthropod based on phase growth paddy from cultivation conventional and ICM. The experiment was conducted in lowland rice agro-ecosystem at two plots with conventional cultivation method and ICM. Sampling of predatory Arthropods was done on the phase growth vegetative and generative paddy using net trap, yellow pan trap, and direct observation in the plants. The results showed that the predatory arthropods found were from Insecta and Arachnida class. The species diversity of predatory arthropod at phase growth of generative was higher than vegetative phase both at the conventional and ICM cultivation. Diversity predatory arthropod on the ICM method was higher compared to conventional. Paddy cultivation method with ICM through the rational use of insecticides can be part of conservation for predatory arthropod species.